A Novel and Simplest Green Synthesis Method of Reduced Graphene Oxide Using Methanol Extracted Vernonia Amygdalina: Large-Scale Production - Bayisa Meka Chufa; Bedasa Abdisa Gonfa; Teketel Yohannes Anshebo; Getachew Adam Workneh (Advances in Condensed Matter Physics)
The large-scale production of high-quality graphene is the major focus of scientists and engineers recently. However, its massive manufacturing routes from its precursor graphene oxide (GO) are involved in the production of toxic gasses and consist of hazardous explosive steps that severely hurt and threaten ecological balance and human health. Therefore, in this study, we investigated the green, effective, and economical approach for the synthesis of graphene by using Vernonia amygdalina (VA) plant leaf extracts for the effective and efficient reduction of GO. The nonexplosive two-step synthesis of GO in a short period of time in the absence of an ice bath was used in this study. The appropriate solvent for the extraction of VA for the green synthesis of graphene was methanol, and the reducing and capping agent in the plant extract was identified to be terpenoids and polyphenols. The graphene/rGO obtained this way was characterized by UV-VIS, XRD, FTIR, SEM, HR-TEM, and EDAX that confirmed the successful reduction of GO to graphene under the hydrothermal process. The HR-TEM images showed the development of few layers of graphene. The FTIR result also shows the complete reduction of GO. Hence, methanol extracted VA leaves consisted of the most appropriate compounds for reducing and capping agent in the green synthesis and could be the preferred method for the large-scale production of graphene-based materials.